Investigating the solid-state assembly of pharmaceutically-relevant N,N-dimethyl-O-thiocarbamates in the absence of labile hydrogen bonds - Tan, Davin (2021)
There are many active pharmaceutical ingredients that lack N-H, O-H and S-H hydrogen-bond donor functional groups. N,N-disubstituted O-thiocarbamates are examples of molecules that display such a feature. Despite the desirable medicinal properties displayed by some N,N-disubstituted O-thiocarbamates, the study of the solid-state properties of these compounds has been relatively unexplored. Herein, we report the synthesis and analysis of the structures and properties of a series of N,N-dimethyl-O-thiocarbamates, and use X-ray diffraction techniques to gain insight into how these molecules self-assemble in the solid-state. As part of our work, we report for the first time the crystal structure of Tolnaftate, an active pharmaceutical ingredient that is indicated for the treatment of fungal infections. It was observed that the aryl-thiocarbamate C-O bonds are twisted such that the planar aryl and carbamate moieties are orthogonal. Such a non-planar molecular geometry affects the way the molecules pack and crystal structure analyses revealed four general modes in which the molecules can assemble in the solid-state, with some members of the series displaying isostructural relationships. Computational modelling of the cohesive energy densities in the crystals suggests that there is no single stacking type that is associated with greater stability. However, crystals with a combination of high packing index and π···π stacking interactions appear to display large cohesive energy densities. The lack of strong hydrogen bonding interactions in the crystals also leads to relatively low Young’s moduli that are within a narrow range of 10-15 GPa for all 14 crystal structures reported.